Expression Analyses Revealed Thymic Stromal Co-Transporter/Slc46A2 Is in Stem Cell Populations and Is a Putative Tumor Suppressor - Kim, K.Y., Inha University, Incheon, Republic of Korea; Lee, G., Washington University School of Medicine, MO, USA; Yoon, M., Inha University, Incheon, Republic of Korea; Cho, E.H., Inha University, Incheon, Republic of Korea; Park, C.S., University of Ulsan College of Medicine, Asan Medical Center, Seoul, Republic of Korea; Kim, M.G., Inha University, Incheon, Republic of Korea (Molecules and cells, 2015)
By combining conventional single cell analysis with flow cytometry and public database searches with bioinformatics tools, we extended the expression profiling of thymic stromal cotransporter (TSCOT), Slc46A2/Ly110, that was shown to be expressed in bipotent precursor and cortical thymic epithelial cells. Genome scale analysis verified TSCOT expression in thymic tissue- and cell type- specific fashion and is also expressed in some other epithelial tissues including skin and lung. Coexpression profiling with genes, Foxn1 and Hoxa3, revealed the role of TSCOT during the organogenesis. TSCOT expression was detected in all thymic epithelial cells (TECs), but not in the CD31+ endothelial cell lineage in fetal thymus. In addition, ABC transporter-dependent side population and Sca-1+ fetal TEC populations both contain TSCOT-expressing cells, indicating TEC stem cells express TSCOT. TSCOT expression was identified as early as in differentiating embryonic stem cells. TSCOT expression is not under the control of Foxn1 since TSCOT is present in the thymic rudiment of nude mice. By searching variations in the expression levels, TSCOT is positively associated with Grhl3 and Irf6. Cytokines such as IL1b, IL22 and IL24 are the potential regulators of the TSCOT expression. Surprisingly, we found TSCOT expression in the lung is diminished in lung cancers, suggesting TSCOT may be involved in the suppression of lung tumor development. Based on these results, a model for TEC differentiation from the stem cells was proposed in context of multiple epithelial organ formation.